SOSIALISASI PENERAPAN KOMPOR SURYA SEDERHANA SOLUSI ENERGI RAMAH LINGKUNGAN DI LINGKUNGAN MASYARAKAT PEDESAAN - Mauladi Syahra, Rika; Abdullah Mu'arif, Salman; Lukitasari, Nancy; Raudatul Janah, Siti; Sobirin (CV SWA Anugerah, 2024)
This community service activity aims to introduce simple solar stove technology as a renewable energy solution that is environmentally friendly to the community of Desa Balir, which still relies on fossil fuels for cooking. Outreach, training, and demonstrations were carried out to provide knowledge and practical skills on the making and usage of solar stoves. The results of this activity showed a significant increase in public understanding, with over 85% of participants comprehending how solar stoves work and 90% of participants expressing interest in applying this technology in their homes. This activity successfully raised awareness among the community about the importance of renewable energy in supporting environmental conservation and reducing dependence on fossil fuels. Keywords: Solar stove, renewable energy, environmental conservation.